INVESTIGATING THE EFFECT OF USING PODCAST ON STUDENTS’ LISTENING COMPREHENSION - Muhammad Rizky Widodo; Agus Gunawan (Lingua, 2019)
This research entitled “Investigating The Effect Of Using Podcast On Grade Ten Students’ Listening Comprehension At SMA Angkasa 2 Jakarta” principally aims to investigate whether or not Podcast significantly effects on Students’ Listening Comprehension. The research samples were taken using cluster random sampling, with the total number of samples being 60 students. The location of this research was SMA Angkasa 2 Jakarta. The research methodology adopted was quasi-experimental method, with the research design being post-test only control group design. To collect the data, the students were given objective test, numbering 30 items. The research data were analyzed descriptively and inferentially. The findings indicated that there was significant difference of post-test score between the students who were taught using Podcast and students who were taught without using Podcast. It can be seen from the data analysis using ANOVA that showed significance value (sig. 0.010) is lower than < 0.05.It means that Podcast has significant effect on Students’ Listening Comprehension.